PENGARUH BUDAYA DALAM PEMILIHAN TEMPAT BERSALIN PADA IBU HAMIL DI FASILITAS KESEHATAN DI WILAYAH KERJA PUSKESMAS ROKAN I KOTO I - Sri Wulandari; Handayani, Eka Yuli; Fitria, Rahmi; Aldriana, Nana; Andria (Maternity and Neonatal : Jurnal Kebidanan, 2024)
Preparation for childbirth is important in planning a safe place and birth attendant. The best delivery is carried out in a health facility and assisted by health workers. Socio-cultural factors include people’s choice and trust in birth attendants which is still quite high. This research method is quantitative analytical with the research design used being a survey method with a cross sectional design. Data collection uses primary data using a filled-in questionnaire, while data analysis uses the chi-square test. The population of this study was all mothers giving birth in 2022 in the Rokan IV Koto I Community Health Center Working Area. The sample in this study was 80 mothers giving birth in 2022. The results of this research showed a relationship between social culture (p=0.000) on the decision to choose a place to give birth. The conclusion of this research is that there is a socio-cultural relationship to the choice of place of birth. It is hoped that the community health center can provide information so that all pregnant women give birth in health facilities.